2007
DOI: 10.1158/0008-5472.can-07-0188
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Irradiation Induces Mitochondrial-Dependent 53BP1 Protein Relocalization in Irradiated and Bystander Cells

Abstract: The accepted paradigm for radiation effects is that direct DNA damage via energy deposition is required to trigger the downstream biological consequences. The radiation-induced bystander effect is the ability of directly irradiated cells to interact with their nonirradiated neighbors, which can then show responses similar to those of the targeted cells. p53 binding protein 1 (53BP1) forms foci at DNA double-strand break sites and is an important sensor of DNA damage. This study used an ionizing radiation micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
141
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 38 publications
(44 reference statements)
8
141
0
Order By: Relevance
“…This study, together with several other studies (Lyng et al, 2000(Lyng et al, , 2002Limoli et al, 2003;Maguire et al, 2005;Murphy et al, 2005;Nugent et al, 2007;Tartier et al, 2007;Chen et al, 2008), suggested that mitochondria represent the sensor of radiationinduced ionisation events. In this study, we showed that Cyt c-null cells can respond to radiation normally in ROS/NO generations as Cyt c-normal cells (Figures 2B and 3B).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This study, together with several other studies (Lyng et al, 2000(Lyng et al, , 2002Limoli et al, 2003;Maguire et al, 2005;Murphy et al, 2005;Nugent et al, 2007;Tartier et al, 2007;Chen et al, 2008), suggested that mitochondria represent the sensor of radiationinduced ionisation events. In this study, we showed that Cyt c-null cells can respond to radiation normally in ROS/NO generations as Cyt c-normal cells (Figures 2B and 3B).…”
Section: Discussionsupporting
confidence: 79%
“…British Journal of Cancer (2009Cancer ( ) 100, 1912Cancer ( -1916 Mitochondria are pivotal cellular organelles for they not only generate the cellular ATP through oxidative phosphorylation but also initiate the intrinsic apoptosis (Li et al, 2000;Berg and Stryer, 2002). In recent years, emerging evidence indicated that mitochondria have also been implicated in radiation-induced bystander effect (RIBE) (Lyng et al, 2000(Lyng et al, , 2002Limoli et al, 2003;Maguire et al, 2005;Murphy et al, 2005;Nugent et al, 2007;Tartier et al, 2007). Earlier, we reported that cells deficient in mitochondrial DNA (mtDNA) showed a significant reduction of bystander signalling .…”
mentioning
confidence: 99%
“…There have been many studies on membrane signaling in bystander cells (41,(50)(51)(52)(53). Rapid membrane signaling, calcium signaling and ROS induction has been reported previously in unirradiated cells after the addition of ICCM (41).…”
Section: Discussionmentioning
confidence: 93%
“…ATP can pass across gap junctions and hemichannels (Evans et al, 2006) and stress stimuli, including radiation, induce ATP release from cells (Tsukimoto et al, 2010). Thus, ATP released by irradiated cells, for example, through mitochondrial damage (Tartier et al, 2007), might be a candidate signaling molecule in the initiation of oncogenic bystander damage in vivo.…”
Section: Resultsmentioning
confidence: 99%